2015
DOI: 10.1080/17430437.2016.1116167
|View full text |Cite
|
Sign up to set email alerts
|

The promises and pitfalls of sex integration in sport and physical culture

Abstract: Scholars working in the academic field of sport studies have long debated the relationship between modern sport and gender (e.g. Hargreaves 1994; Hargreaves and Anderson 2014;Lenskyj 1986;Messner 2002). Within this body of work, modern sport forms -along with a great diversity of related activities, including dance, fitness training and physical education -have consistently been shown to carry meanings relative to the structures of gender prevailing in the wider social settings within which they take place, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 52 publications
0
32
0
3
Order By: Relevance
“…As such, we contend that the insights advanced in this paper can contribute to wider discussions about gender power relations in sex-integrated sports, martial arts (Channon et al, 2016) and popular forms of physical culture and lifestyle sports (Wheaton, 2004). Our contribution will be particularly useful, as these practices represent relevant and increasingly popular sites where gender and physical cultures are produced, consumed and played out.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we contend that the insights advanced in this paper can contribute to wider discussions about gender power relations in sex-integrated sports, martial arts (Channon et al, 2016) and popular forms of physical culture and lifestyle sports (Wheaton, 2004). Our contribution will be particularly useful, as these practices represent relevant and increasingly popular sites where gender and physical cultures are produced, consumed and played out.…”
Section: Discussionmentioning
confidence: 99%
“…Con el fin de cambiar las relaciones de género y conseguir un deporte más igualitario (Gubby y Wellard, 2015), también se ha enfatizado sobre la necesidad de que la oferta sea integrativa, ofreciendo actividades 'neutrales' como el Korfball, donde participan juntos hombres y mujeres. Sin embargo, en la actualidad se sigue recalcando la necesidad de realizar cambios en la promoción de las AFD dirigidas a mujeres para impulsar de esta manera la integración sexual (Channon et al, 2016).…”
Section: Mujer Y Deporte | Women and Sportsunclassified
“…Different studies have found that promoting physical-recreational activity among women is extraordinarily important because of the benefits it brings them (Taylor, Hughes, & Koufaki, 2013). However, according to gender relations and the gender order, different perspectives have been found on how to organise and carry out programmes in reference to the composition of the groups of practitioners (Channon, Dashper, Fletcher, & Lake, 2016). On the one hand, some authors underscore the need to offer physical-sport activity (PSA) programmes exclusively for women in order to promote their participation (Gehring, 2005;McDermott, 2004;Taylor, 2014;Whittington, 2006;Whittington, Mack, Budbill, & Mc Kenney, 2011).…”
Section: Programas Recreativos Exclusivos Para Mujeresmentioning
confidence: 99%
See 1 more Smart Citation
“…(Hargreaves;Anderson, 2014). A integração de homens e mulheres em equipes esportivas representa um avanço no que tange à desconstrução social do gênero, segundo Channon et alii (2015). Os autores apontam que as experiências vivenciadas, quer sejam no contexto dos treinamentos, ou em situações de jogo, favorecem mudanças de atitude que repercutem em outros setores, como o social, o pessoal e, até mesmo, no âmbito do trabalho, relacionado ao reconhecimento das diferentes capacidades e habilidades femininas.…”
unclassified